2015
DOI: 10.1155/2015/981274
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Effects of Different Mydriatics on Choroidal Thickness by Examining Anterior Chamber Parameters: The Scheimpflug Imaging and Enhanced Depth Imaging-OCT Study

Abstract: Aim. To assess the effects of mydriatics commonly used in clinical practice on choroidal thickness and anterior chamber change. Methods. This was a prospective, randomized, controlled, double-blinded study including a single eye of the participants. The subjects were assigned into 4 groups to receive tropicamide 1%, phenylephrine 2.5%, cyclopentolate 1%, and artificial tears. At the baseline, anterior chamber parameters were assessed using a Pentacam Scheimpflug camera system, and choroidal thickness (CT) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 22 publications
6
43
0
Order By: Relevance
“…Since the time-point to measure the ChT varied among the previous studies, it is recalculated as the time after the first instillation of eye drops, in order to facilitate the comparison ( Table 4 ). In agreement with the present study, Kara et al [ 25 ] and Yuvacj et al [ 26 ] both reported decreased SFChT after administration of 1% tropicamide or 2.5% phenylephrine alone. On the other hand, Kim et al [ 27 ] failed to observe significant changes in SFChT with the same agent used in the present study (0.5% tropicamide plus 0.5% phenylephrine).…”
Section: Discussionsupporting
confidence: 93%
“…Since the time-point to measure the ChT varied among the previous studies, it is recalculated as the time after the first instillation of eye drops, in order to facilitate the comparison ( Table 4 ). In agreement with the present study, Kara et al [ 25 ] and Yuvacj et al [ 26 ] both reported decreased SFChT after administration of 1% tropicamide or 2.5% phenylephrine alone. On the other hand, Kim et al [ 27 ] failed to observe significant changes in SFChT with the same agent used in the present study (0.5% tropicamide plus 0.5% phenylephrine).…”
Section: Discussionsupporting
confidence: 93%
“…The choroid's thickness has been shown to be sensitive to a range of pharmacological agents, including nicotine, sildenafil citrate, ranibizumab, triamcinolone acetonide, and cholinergic agents . Among cholinergic agents, some antimuscarinics (1% atropine, 2% homatropine, and 1% cyclopentolate) have been reported to significantly increase subfoveal choroidal thickness in humans.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, there are some reports that highlight the effect of topical anticholinergic or adrenergic agents on choroidal thickness with varied or even contradictory findings. For example, some studies have reported absence of any influence of these agents on the choroidal thickness 6 7 8 , while some authors have observed an increase 9 or a decrease 10 11 in the choroidal thickness, even when the same drugs were used ( Table 1 ). We speculate that such discrepancies might arise from the differences in the methods of drug instillation, race of participants, and distribution rate of mydriatic agents to the posterior.…”
mentioning
confidence: 99%